PERBEDAAN GANGGUAN KOGNITIF SUBJEK STROKE ISKEMIK BERDASARKAN SISI HEMIPARESIS - Gabriella Gabriella; Budi Riyanto Wreksoatmodjo; Andre Andre (PERDOSNI, 2020)
DIFFERENCE OF COGNITIVE IMPAIRMENT IN ISCHEMIC STROKE PATIENTS BASED ON HEMIPARESIS SIDEABSTRACTIntroduction: Cognitive impairment in stroke has a significant impact on the quality of life and is different from the location of the lesion. Patients with a lesion in the left cerebral hemisphere tend to have cognitive impairment and dementia.Aim: This study investigates the relationship between the location of the lesion, which is manifested by hemiparesis side, and the occurrence of cognitive impairment in ischemic stroke patients.Method: A cross-sectional study was conducted in the population of ischemic stroke patients at Atma Jaya Hospital, who were registered from January 2014 to December 2018. Cognitive function was measured by the Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment Indonesian Version (MoCA-Ina). Data were analyzed univariate and bivariate with the software program, statistical package for the social sciences (SPSS) version 25.0.Result: There were 125 patients included in this study, which predominantly was 55 years old and older (62.4%) and had a low education level (58.4%). The proportion of patients with right-sided hemiparesis (54.4%) was slightly higher than the left-side one (45.6%). No significant relationship was observed between the hemiparesis side and every cognitive function domain measured by MMSE and MoCA-Ina (p-value >0.05).Discussion Hemiparesis side indicating hemisphere lateralization in ischemic stroke patients showed no significant relationship with the occurrence of cognitive impairment based on MMSE and MoCA-Ina score. Keywords: Cognitive impairment, hemisphere lateralization, ischemic stroke, MMSE score, MoCA-Ina scoreABSTRAKPendahuluan: Gangguan kognitif pada stroke menyebabkan penurunan kualitas hidup dan berbeda berdasarkan letak lesi. Berdasarkan letak lesi, lesi di hemisfer serebri kiri lebih sering menyebabkan gangguan kognitif dan demensia.Tujuan: Tujuan penelitian untuk mengetahui pengaruh perbedaan letak lesi dilihat dari sisi hemiparesis terhadap gangguan kognitif pada subjek stroke iskemik.Metode: Studi potong lintang dilakukan pada pasien stroke iskemik di RS Atma Jaya periode tahun 2014- 2018. Fungsi kognitif dinilai dengan menggunakan Mini Mental State Examination(MMSE) danMontreal Cognitive Assesment Indonesian Version(MoCA-Ina). Analisis data dilakukan secara univariat dan bivariat menggunakan menggunakan program sStatistical pPackage for the sSocial sSciences (SPSS) versi 25.0.Hasil: Sebanyak 125 pasien tergabung dalam penelitian ini, yang sebagian besar berusia ≥55 tahun (62,4%) dan memiliki tingkat pendidikan <9 tahun (58,4%). Proporsi pasien dengan hemiparesis kanan (54,4%) lebih besar daripada kiri (45,6%). Tidak terdapat hubungan antara sisi hemiparesis dengan skor MMSE dan MoCA-Ina pada semua ranah (nilai p >0,05).Diskusi: Sisi hemiparesis pasien stroke iskemik yang menunjukkan lateralisasi hemisfer serebri tidak berhubungan dengan gangguan kognitif berdasarkan skor MMSE dan MoCA-Ina.Kata kunci: Gangguan kognitif, lateralisasi hemisfer, skor MMSE, skor MoCA-Ina, stroke iskemik